Utilization of some non coded amino acids as isosters of peptide building blocks - Hlaváček, J; Marcová, R; Ježek, R; Slaninová, J (Amino acids, 1996)
In our study on non coded amino acids and their utilization in peptide chemistry we synthesized methylene-thio (CH2-S) and methyleneoxy (CH2-O) group containing amino acids and pseudodipeptides which could be used as building blocks for the construction of peptide hormone analogues. The (CH2-S) isoster of peptide bond exhibits increased flexibility, lipophility and resistance to proteolytic enzymes. This group exhibits similar properties as the isosteric disulfide bond in the side chain of cystine residue. The (CH2-O) isoster is moreover similar in its geometry to extended conformation of peptide bond. As a consequence, the changed profile of biological activities could be expected for peptide hormone analogues containing such isosteric moiety. The (CH2-S) isosters of the peptide bond were prepared by alkylation of thiolates of 2-mercaptocarboxylic acids, the disulfide bond by alkylation of cysteine or homocysteine. The (CH2-O) isosters were prepared by (AcO)4Rh2 catalyzed addition of carbenes of alkyl diazocarboxylates to N-protected aminoalcohols. Pseudodipeptides H-Leu-ψ(CH2-S)-Gly-NH2 and H-Leu-ψ(CH2-O)-Gly-NH2 were introduced into the C-terminal part of the oxytocin molecule using solution methods of peptide chemistry. Both inserted isosteric bonds were resistant against proteolytic degradation, the first one was found to decrease an enzymic cleavage of the distant Tyr(2)-Ile(3) bond in the corresponding analogue, too. The (CH2-S) isosters of the disulfide bond containing an orthogonal protection of theirα-amino (Fmoc) andα-(OAll, OH) orω-(OBu(+), OH) carboxylic groups were applied in the solid phase synthesis of the aminoterminal 1-deamino-15-pentadecapeptide of endothelin-I which represents a strong vasoactive agent. The solid phase synthesis was carried out by the step-wise protocol on the Rink or Merrifield type resin using orthogonally protected carba cystine building blocks.